Assessing Aquatic Landscape Health Using Brachyuran Crab Habitats in the Chennai Coastal Region: A Case Study - Jayaprakash, Jayanthi; Jacob, Akil; Ranjitha, Jeevanandam; Ragunathan, Manickavalli Gurunathan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study focuses on the marine brachyuran crab species habitat used as a biosensor for aquatic landscape analysis in the Chennai region. Brachyuran crabs have been recognized as potential biosensors owing to their sensitivity to environmental changes and specific habitat requirements. By analyzing their distribution patterns and abundance, valuable insights can be gained regarding the overall health and quality of aquatic landscapes in the Chennai region. This study aimed to explore the feasibility of utilizing brachyuran crabs as indicators for assessing the ecological conditions of Chennai's marine ecosystems. A significant finding of this study is that we assessed aquatic landscape health using marine brachyuran crab habitats, and identified that Chennai’s marine landscape is dominated by a soft substrate region, followed by a region that has a mixture of soft and hard substrates, and then by estuary and mangrove substrates. The findings from this research could potentially assist in the development of effective management strategies and conservation measures to protect and sustain diverse marine life in Chennai's coastal waters and marine landscape types in the Chennai region.